2017
DOI: 10.17267/2317-3386bjmhh.v5i4.1472
|View full text |Cite
|
Sign up to set email alerts
|

Blue Ligth Emitting Diode in Treatment of Recurring Vulvovaginal Candidiasis: A Case Report

Abstract: Introduction:Recurring vulvovaginal candidiasis (RVVC) is an infectious disease of the lower genitourinary tract, that occurs at least 4 times per year. Drug treatment can last months and favor the appearance of adverse effects and increase the chances of recurrence. Blue Light Diode (LED) is an electromagnetic spectrum light, with antimicrobial functions. Case Report: A case report was made of a patient with RVVC whose treatment consisted of three sessions of 60-minutes each, of application of blue LED in int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Three sessions were performed, which reduced the fungal load at the end of treatment. Three months after the conclusion of the treatment, the absence of fungal infection was noted [20]. They also observed resolution of the clinical manifestations (pruritus, burning, dysuria, dyspareunia, and edema) of the patient after treatment.…”
Section: Discussionmentioning
confidence: 86%
“…Three sessions were performed, which reduced the fungal load at the end of treatment. Three months after the conclusion of the treatment, the absence of fungal infection was noted [20]. They also observed resolution of the clinical manifestations (pruritus, burning, dysuria, dyspareunia, and edema) of the patient after treatment.…”
Section: Discussionmentioning
confidence: 86%
“…These fluences were adjusted after initial experiments based on the study described elsewhere. 24 According to the manufacturer's instructions, a 5-minute break is taken every 10 minutes to allow the instrument to cool. The positive control consists of a yeast suspension in the presence of an antifungal agent with a 50% growth inhibitory concentration (IC50).…”
Section: Leds Applicationmentioning
confidence: 99%
“…9 Research group recently published a case report that demonstrated a response to recurrent vulvovaginal candidiasis and the post-radiation treatment long-term sequelae (in press). 10,11 A clinical trial for recurrent vaginal candidiasis is ongoing. We previously conducted a pilot study with noncancer post-menopause syndrome patients with promising results (in press) with three sessions with a LED device and good tolerance was observed.…”
mentioning
confidence: 99%